Seagrass ecosystem response to long-term high CO2 in a Mediterranean volcanic vent - Apostolaki, Eugenia T.; Vizzini, Salvatrice; Hendriks, Iris E.; Olsen, Ylva S. (Marine Environmental Research, 2014)
We examined the long-term effect of naturally acidified water on a Cymodocea nodosa meadow growing at a shallow volcanic CO2 vent in Vulcano Island (Italy). Seagrass and adjacent unvegetated habitats growing at a low pH station (pH = 7.65 ± 0.02) were compared with corresponding habitats at a control station (pH = 8.01 ± 0.01). Density and biomass showed a clear decreasing trend at the low pH station and the below- to above-ground biomass ratio was more than 10 times lower compared to the control. C content and δ13C of leaves and epiphytes were significantly lower at the low pH station. Photosynthetic activity of C. nodosa was stimulated by low pH as seen by the significant increase in Chla content of leaves, maximum electron transport rate and compensation irradiance. Seagrass community metabolism was intense at the low pH station, with significantly higher net community production, respiration and gross primary production than the control community, whereas metabolism of the unvegetated community did not differ between stations. Productivity was promoted by the low pH, but this was not translated into biomass, probably due to nutrient limitation, grazing or poor environmental conditions. The results indicate that seagrass response in naturally acidified conditions is dependable upon species and geochemical characteristics of the site and highlight the need for a better understanding of complex interactions in these environments. © 2014 Elsevier Ltd. The study was funded by the EU FP7 project MedSeA (Grant Agreement No. 265103). Peer Reviewed